Selective inhibition of CYP2C8 by fisetin and its methylated metabolite, geraldol, in human liver microsomes. Issue 2 (April 2018) - Shrestha, Riya; Kim, Ju-Hyun; Nam, Wongshik; Lee, Hye Suk; Lee, Jae-Mok; Lee, Sangkyu
Abstract: Fisetin is a flavonol compound commonly found in edible vegetables and fruits. It has anti-tumor, antioxidant, and anti-inflammatory effects. Geraldol, the O -methyl metabolite of fisetin in mice, is reported to suppress endothelial cell migration and proliferation. Although the in vivo and in vitro effects of fisetin and its metabolites are frequently reported, studies on herb–drug interactions have not yet been performed. This study was designed to investigate the inhibitory effect of fisetin and geraldol on eight isoforms of human cytochrome P450 (CYP) by using cocktail assay and LC-MS/MS analysis. The selective inhibition of CYP2C8-catalyzed paclitaxel hydroxylation by fisetin and geraldol were confirmed in pooled human liver microsomes (HLMs). In addition, an IC50 shift assay under different pre-incubation conditions confirmed that fisetin and geraldol shows a reversible concentration-dependent, but not mechanism-based, inhibition of CYP2C8. Moreover, Michaelis-Menten, Lineweaver-burk plots, Dixon and Eadie-Hofstee showed a non-competitive inhibition mode with an equilibrium dissociation constant of 4.1 μM for fisetin and 11.5 μM for geraldol, determined from secondary plot of the Lineweaver-Burk plot. In conclusion, our results indicate that fisetin showed selective reversible and non-competitive inhibition of CYP2C8 more than its main metabolite, geraldol, in HLMs. Graphical abstract: